Political Economy of Lampung Black Pepper and Local Resistance, Colonial to Japanese Occupation - Shadra, M. Nehza Rausan (Siginjai: Jurnal Sejarah, 2026)
Lampung black pepper has been a strategic commodity linking Sumatra's hinterland to global trade networks from the Srivijaya era to the Japanese occupation. This study aims to trace the political economy dynamics of pepper trade in Lampung and to uncover forms of local resistance emerging in response to monopolistic and colonial exploitation systems. A descriptive qualitative method with a historical case study approach was employed, utilizing socio-economic history and colonial resistance theory. Data were collected through literature review of primary sources such as the Bojong Charter (1691), Sukau Charter (1695), VOC reports, Dutch colonial archives, and relevant secondary sources. The findings reveal that control over Lampung black pepper by the Banten Sultanate, VOC, and Dutch East Indies systematically shaped an unequal social structure through policies of verplichte leverantie and contingentenstelsel. This economic pressure triggered a layered spectrum of resistance, ranging from armed rebellions led by Radin Inten I-II and Radin Imba Kesuma, spiritual movements of Syattariyah and Naqsyabandiyah orders, to everyday resistance such as smuggling and sabotage. The study concludes that pepper not only served as an instrument of external domination but also acted as a catalyst for the formation of socio-political consciousness and resistance identity among Lampung communities.